On new physics in Delta Gamma(d) - Bobeth, C; Haisch, U; Lenz, A; Pecjak, B; Tetlalmatzi-Xolocotzi, G (Springer Verlag, 2014)
Motivated by the recent measurement of the dimuon asymmetry by the DØ collaboration, which could be interpreted as an enhanced decay rate difference in the neutral B d -meson system, we investigate the possible size of new-physics contributions to ΔΓ d . In particular, we perform model-independent studies of non-standard effects associated to the dimension-six current-current operators (d̄p) (p̄′b) with p, -rfpag′ = u, c as well as (d̄p) (τ̄τ). In both cases we find that for certain flavour or Lorentz structures of the operators sizeable deviations of ΔΓ d away from the Standard Model expectation cannot be excluded in a model-independent fashion. © 2014 The Author(s).